Coronary Artery Wall ThicknessandLumen Diameter of Nicotine-Induced White Rats (Rattus norvegicus) - Nur Anisah; Maya Nurwartanti Yunita; Hani Plumeriastuti; Bodhi Agustono; Reina Puspita Rahmaniar (The Indian Veterinary Journal, 2023)
Nicotine can cause hemodynamic disorders for good health. This study aimed to observe the histopathology of lumen diameter and coronary artery wall thickness in white rats exposed to nicotine. Rats were divided into five treatment groups, C (without nicotine exposure), T1,T2,T3, and T4 (nicotine concentration 0,005mg/ml; 0,05mg/ml; 0,2mg /ml, and 0.65 mg/ml). The results showed a significant difference in coronary artery wall thickness between the control and treatment groups. The diameter of the coronary artery lumen was narrowed. In conclusion, a higher concentration of nicotine can increase the thickness of the coronary artery wall and decrease the lumen diameter.